Spring sown camelina (Camelina sativa) contributes to the management of three summer weeds - Codina Pascual, Noemí; Torra, Joel; Baraibar, Bàrbara; Royo-Esnal, Aritz (Italian Journal of Agronomy, 2024)
Camelina (Camelina sativa (L.) Crantz) is an attractive drought-tolerant crop for Mediterranean regions due to its rapid growth and ability to out-compete many dicotyledonous winter annual weeds. In this experiment the weed suppression capacity of spring sown camelina against Chenopodium album L. (common lambsquarters), Polygonum aviculare L. (prostrate knotweed), and Xanthium spinosum L. (spiny cocklebur) was studied. The trial was conducted in Lleida (Spain) between 2019 and 2021, and camelina was sown in March each year. Experimental plots contained quadrats with each weed species as well as weed-free and crop-free quadrats. Height and aboveground biomass of weeds in competition with camelina decreased by over 50% compared to the controls. However, crop and weed growth had seasonal differences depending on the weather conditions: (1) a moderately dry spring promoted crop production (1573 kg ha-1); (2) a rainy spring benefited weed development, negatively affecting crop growth and yield (739 kg ha-1); and (3) a severe dry spring affected growth of both crop and weeds, reducing crop production by up to 80% (298 kg ha-1). The summer weed suppression capacity of camelina is enhanced by drought conditions, which makes camelina useful for managing these weeds.